Heterogeneity of demoralization syndrome in Chinese cancer patients: an optimal cut-off threshold for the demoralization scale - Li, Yanhua; Liu, Xiaoxin; Yang, Qun (Frontiers in Psychiatry, 2025)
BackgroundThe development of numerous demoralization assessment tools has significantly contributed to the field, with the Demoralization Scale being the most frequently utilized. Nevertheless, the inconsistency in cutoff values for these tools hinders accurate estimation of demoralization, underscoring the need for research to determine an optimal threshold. This study examined the heterogeneity of demoralization syndrome among cancer patients in China, aiming to establish an optimal cut-off value for the mandarin version demoralization scale.MethodA cross-sectional study recruited 971 cancer patients from Hunan Province between June 14, 2022 and June 13, 2023. Latent profile analysis was used to identify distinct profiles, and receiver operating characteristic curve analysis determined the optimal cut-off point.ResultThree distinct profiles were identified: “minimal demoralization - meaningful” (22.3%), “moderate demoralization” (59.9%), and “severe demoralization - hopelessness” (17.9%). The mandarin version demoralization scale showed high accuracy (AUC = 0.995) with an optimal cut-off point of 23.5 (sensitivity: 98.9%, specificity: 94.8%, and accuracy: 93.7%).ConclusionThe distinct profiles highlight varying demoralization syndrome in cancer patients. Notably, the Mandarin Version Demoralization Scale exhibits excellent properties, with a cutoff of 23.50 for Chinese cancer patients. Our study deepens understanding, offering insights for standardized clinical classifications, enabling cross-setting comparisons.